The Impacts of Human Resource Management Practices on Employee Retention in Kulim Industrial Estate - Ayaru, Visithira Barathi (2012)
Employee Retention is one of the common challenges facing by most of the organization currently. The main objective of this study is to examine the relationships between human resource management (HRM) practices and employee retention. There are four dimensions of HRM practices namely compensation, benefits and rewards, performance appraisal, training and career development and work environment. A total of 200 questionnaires were distributed to all level of employees in Kulim Industrial Estate (KIE), Malaysia and 156 questionnaires were returned and used for data analysis. Pearson Correlation analysis been done to assess the relationships of all the variables. The outcome of findings showed a positive and significant correlation of all HRM practices and employee retention. Discussions explained the significance of each HRM practices in supporting employee retention in KIE. Eventually, conclusion and recommendations were mentioned.